Subordinate Fish Mediate Aggressiveness Using Recent Contest Information - Hotta, Takashi; Awata, Satoshi; Jordan, Lyndon A.; Kohda, Masanori (Frontiers in Ecology and Evolution, 2021)
Memorizing dominance relationships can help animals avoid unwinnable subsequent contests. However, when competitive ability changes over time—for example, as a function of condition—it may be adaptive to ‘forget’ these dominance relationships and for subordinates to once again enter contests with previously dominant individuals. Here, we examined the behavior of pairs of male cichlid fish, Julidochromis transcriptus, in repeated contests separated by different time intervals. We found that the time taken to reach resolution of dominance relationships influenced subsequent aggressive behavior of the subordinate towards the dominant, with longer initial contests leading to higher subsequent aggression. Longer time intervals between contests also increased aggression from the subordinate towards the dominant. These results are consistent with increasing uncertainty due to ambiguous contest outcomes and increasing time intervals. Our results also show that a longer time was necessary to resolve contests between larger pairs, suggesting a self-assessment strategy, but not a mutual assessment strategy. Taken together, larger individuals appear to adaptively lose or ignore previously gathered social information because they have a higher fighting ability and better body condition. Therefore, we conclude that losing or ignoring unreliable information may be an adaptive strategy in the context of dominance relationships.